Dietary chitooligosaccharide supplementation improves mineral deposition, meat quality and intramuscular oxidant status in broilers. (28th September 2022) - Li, Jun; Wang, Shiqi; Chen, Yueping; Cheng, Yefei; Wen, Chao; Zhou, Yanmin
Abstract: BACKGROUND: The present study aimed at evaluating the in vitro adsorption capability of chitooligosaccharide (COS) with some metal elements (Fe, Zn, Cd, Pb) at different pH values along with potential effects of dietary COS supplementation on growth performance, mineral content, meat quality and oxidant status in broilers. Day‐old male chicks were randomly distributed into two groups and offered a basal diet supplemented with or without 30 mg kg −1 COS for 42 days. RESULTS: In vitro trials demonstrated that Fe levels were higher ( P < 0.001) in the COS‐treated group compared with the non‐treated group at pH of 2.5. However, these levels became lowered when pH values were raised to 5 ( P < 0.01) or 6 ( P < 0.001). Similarly, COS adsorbed more ( P < 0.05) Zn at pH values of 2.5 and 6, and Cd contents at pH of 2.5 for 70 min when compared with the control. For in vivo trial, the feed‐to‐gain ratio, serum Cu ( P < 0.01), hepatic Mn, Cr ( P < 0.05) and intramuscular Cd ( P < 0.01) were lower in response to COS treatment. Supplementation of COS improved ( P < 0.05) meat quality of broilers in terms of lower drip loss, cooking loss and malondialdehyde content with a concomitant increase ( P < 0.01) in the pH of breast meat at 24 h post mortem. CONCLUSION: COS adsorbed heavy metal ions not only in vitro but also in broilers, and dietary supplementation with 30 mg kg −1 COS improved growth performance, breast meat quality and oxidant status in broilers. © 2022 Society of Chemical Industry.